Decision systems redux. Issue 1 (2nd January 2019) - Power, Daniel J.; Heavin, Ciara; Keenan, Peter
ABSTRACT: Looking forward, the goal of this article is to stimulate discussion and encourage novel thinking about computerized systems. Looking back 60 years, this article reviews definitions and research related to the decision system concept and associated terms like automated decision system (ADS) and decision support system (DSS). This historical perspective differentiates and expands the phenomenon of a decision system to create a modern context for future applied and scholarly research and development. Looking forward, more automated decision systems will make and implement decisions. Analytics will be embedded in decision systems, decision support will proliferate, and decision systems will be part of ambient intelligent environments. This article expands the horizon for decision-making research by reviving the concept of a decision system. Perhaps this article will lead researchers to study decision systems more comprehensively.